Delayed Motor Development and Infant Obesity as Risk Factors for Severe Deformational Plagiocephaly: A Matched Case–Control Study - Kim, Eun-Hee; Kim, Ki Eun; Jeon, Jihyun; Sheen, Youn Ho; Lee, Hyun-Seung; Yoon, So Young; Kim, Nam Hyo; Choi, Kyoung Min (Frontiers in Pediatrics, 2020)
The prevalence of deformational plagiocephaly (DP) has increased since the recommendation of positioning infants to their back during sleeping and is affected by various biological and environmental factors. This study aimed to investigate associations between DP and perinatal or infant characteristics, including obesity. This case-control study included 135 infants (81 males) aged 2–12 months who were diagnosed with DP using calculated cranial vault asymmetric index and cranial index and 135 age- and sex-matched controls. Motor development was evaluated using the Alberta Infant Motor Scale, and obesity was defined by body mass index. Univariate and multivariate logistic regression models were used to assess potential risk factors for DP and its severity. One hundred thirty-five infants with DP were divided into the following three subgroups according to severity indicated by the cranial vault asymmetry index: mild to moderate group (n = 87, 64.4%), severe group (n = 48, 35.6%), and a combined plagiocephaly and brachycephaly group (n = 79, 58.5%). Independent risk factors significantly associated with development of DP were bottle-only feeding (adjusted odds ratio [aOR] = 4.65; 95% confidence interval [95% CI]: 2.70-8.00), little tummy time when awake (aOR = 3.51, 95% CI: 1.71-7.21), delay of motor development (aOR = 2.85, 95% CI: 1.08-7.49), and obesity at diagnosis (aOR = 2.45, 95% CI: 1.02-5.90). Among these risk factors, delay of motor development (aOR = 4.91, 95% CI: 1.46-16.51) and obesity at diagnosis (aOR = 4.10, 95% CI: 1.42-11.90) were particularly related to severe DP. In conclusion, this study confirms that DP risk is positively associated with bottle-only feeding, infrequent tummy time, and delayed development of motor milestones. Notably, this study demonstrates infant obesity as a new risk factor for DP. Our findings suggest that obesity should be identified early and managed comprehensively in infants with DP.